2022
DOI: 10.1007/s11270-022-05503-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity of Organic Contaminants in a meso-scaled River System

Abstract: Due to intensive anthropogenic usage, a complex mixture of inorganic and organic contaminants entered and still enters freshwater systems, released by various activities and emission sources. However, because of the highly dynamic nature of rivers, the individual occurrence, fate, and behavior, especially of organic contaminants, are highly complex and not fully understood. Here, a GC/MS non-target screening was applied to identify and determine the chemical diversity in the aqueous phase of the meso-scaled Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 95 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Among others, they are used as technical agents to produce specialty papers and have therefore also been detected in recovered papers and packaging made from recycled paper [7,12]. Further on, DPE is a characteristic compound of wastewaters from modern paper production sites, and both were already found in the water of the Rur river [40]. For the investigated floodplains, the maximum concentrations for Mesamoll ® were 1.3 µg/g TOC in July and 0.75 µg/g TOC in February, for DIPN 14.2 µg/g TOC in July and 4.1 µg/ g TOC in February and for DPE 800 ng/g TOC in July and 13 ng/g TOC in February.…”
Section: Resultsmentioning
confidence: 99%
“…Among others, they are used as technical agents to produce specialty papers and have therefore also been detected in recovered papers and packaging made from recycled paper [7,12]. Further on, DPE is a characteristic compound of wastewaters from modern paper production sites, and both were already found in the water of the Rur river [40]. For the investigated floodplains, the maximum concentrations for Mesamoll ® were 1.3 µg/g TOC in July and 0.75 µg/g TOC in February, for DIPN 14.2 µg/g TOC in July and 4.1 µg/ g TOC in February and for DPE 800 ng/g TOC in July and 13 ng/g TOC in February.…”
Section: Resultsmentioning
confidence: 99%
“…84 A few recent studies have also found ATBC concentrations in various water environments; for example, concentrations were found to be 0.05 µg L −1 in the marine environment of Kuwait, 73 <LOQ to 96 ng L −1 in Nakdong River of Korea, 103 154 µg L −1 in groundwater of England, 104 and ≤0.54 in Rur River of Germany. 105 The most recent peer-reviewed studies have raised concerns about the potential endocrine disruption and developmental toxicity of ATBC in fish species. This is particularly alarming given the increasing ATBC residues in global water bodies, as reported in recent studies above.…”
Section: Emerging or Alternative Plasticizersmentioning
confidence: 99%
“…A few recent studies have also found ATBC concentrations in various water environments; for example, concentrations were found to be 0.05 μg L −1 in the marine environment of Kuwait, 73 <LOQ to 96 ng L −1 in Nakdong River of Korea, 103 154 μg L −1 in groundwater of England, 104 and ≤0.54 in Rur River of Germany. 105…”
Section: An Overview Of Commonly Used Plasticizersmentioning
confidence: 99%
“…The subsequent extraction of water samples was conducted utilizing established and previously documented protocols after Dsikowitzky et al [24] and Schwanen and Schwarzbauer [91].…”
Section: Water Sample Extractionmentioning
confidence: 99%